Variation of Arm Muscle Strength Training in Archery: A Systematic Literature Review - Hakim, Luqman; Adi S (Universitas PGRI Palembang, 2025)
This study is to examine the use of variations in arm muscle strength training in archery because this sport relies heavily on the arm muscles, and physical training for these muscles has a significant impact on the arm muscle strength when pulling the bowstring. The PRISMA guidelines for systematic reviews and meta-analyses were followed in this review investigation. Studies must have been released within the last five years, namely January 2020 to July 2024. The terms used in the search procedure were (1) strength; and (2) archery. The search for this study was conducted using the Scopus research journal database. The findings of this investigation were The overall theme of this study was 97. covering 71 items, 10 of which were selected as relevant. Therefore, it can be said that weight training such as push-ups, pull-ups, and bench dips using tools such as resistance bands and barbells are examples of variations in arm muscle strength training in archery. based on relevant findings, such as improving archery ability, improving muscle strength in archery competitors, improving physical fitness and accuracy in archery competitors, and reducing arm tremors.